EPIGENETIC AND GENETIC ASPECTS OF RETT SYNDROME, ASSOCIATED WITH EPIMUTATION C → mC IN THE TRANSGENERATIONAL INHERITANCE - Kovanova, E.N.; Bihunyak, Т.V.; Bihuniak, K.O.; Kulitska, M.I. (World of Medicine and Biology, 2017)
The C→mC epimutation associated with the formation of methylcytosine in CpG islands occurs under the influence of environmental factors during the gametogenesis in the generation F0 of the boy-grandfather. Epimutation and the replacement of CG on АТ promote the production of defective MeCP2 protein that can deregulate gene expression in the postnatal development of the child's brain. Expression of the phenotype of Rett syndrome in transgenerational inheritance can be observed in the different generations grandson boy due to homozygosity of homologous loci of q28 X and Y chromosomes. As a result of transgenic inheritance in boys and girls of different generations there is a uniallelic and biallelic uniparent dysomia of mat and pat origin.
Keywords: Rett syndrom; pat; mat origin; transgenerational inheritance; epimutation; uniparent dysomia